Green Chemistry Principles in Sustainable Synthesis: A Fundamental Review of Environmentally Benign Reactions - Eko Sutrisno; Verawaty Simarmata (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study develops a theory-driven, non-empirical framework that reconceptualizes green chemistry principles as an integrated architecture for sustainable synthesis. Through systematic literature triangulation and comparative principle-matrix construction, environmentally benign reactions are analyzed across three hierarchical domains: molecular efficiency, process integrity, and systemic impact. The findings indicate that atom economy, catalytic selectivity, solvent engineering, and alternative energy modalities function as mechanistic determinants that reduce intrinsic waste formation. At the operational level, solvent substitution, catalyst recyclability, and energy modulation mediate the conversion of reaction-level improvements into measurable environmental benefits. Systemic evaluation further demonstrates that lifecycle assessment, renewable feedstock integration, and material durability extend sustainability beyond laboratory metrics toward macro-scale ecological and socio-economic relevance. The review advances a multi-level conceptual model that links mechanistic chemistry with sustainability science, transforming normative green principles into analytically operational constructs. By bridging molecular design and lifecycle governance, the study provides a theoretically robust foundation for guiding future innovation in environmentally benign synthetic chemistry.